Studi Deskriptif tentang Penerapan Strategi Discovery Learning dalam Meningkatkan Kemampuan Berpikir Kritis Siswa (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
The objective of this research is to assess the use of discovery learning techniques in enhancing students' engagement and critical thinking abilities in Pancasila and Citizenship Education courses. Discovery learning is a teaching method that encourages students to learn on their own by observing, exploring, and verifying what they learn. The study's findings suggest that the implementation of discovery learning may enhance students' engagement in debates, facilitate inquiry, and encourage the expression of viewpoints. Also, students' critical thinking abilities became better because they could examine material, come to conclusions, and solve issues in a logical way. However, there were several problems with its use, such as not having enough time, students being at different levels of preparation, and problems with managing the classroom. With careful preparation, good time management, and a lot of help for students, these problems may be solved. The discovery learning technique has been shown to be beneficial in enhancing the quality of learning. It is also particularly useful for helping students become active, critical thinkers who can solve issues on their own.